ZLS: A next-door lightweight QoS aware location service technique for VANET on highways - Rehan, M. (Institute of Electrical and Electronics Engineers Inc., 2014)
In VANET, a Location service technique comprises of location update and location request. In location update, a destination vehicle advertises its services and location to a set of vehicles called location servers. In location request, a source vehicle queries location servers in its broadcast range about the location and services of destinations. During location update, separate control messages are exchanged to periodically update location servers which create delay and congestion in the network. Similarly, after location request, pre-loaded digital maps at source vehicle are used to find the shortest path towards destination which does not give vehicle density on road at that moment in time. Other than digital maps, Dijkstra or Bellmen ford algorithms at source or intermediate nodes are also used to find shortest path, which is a computationally time consuming activity leading to an extra delay during path finding and before packet transmission. We therefore propose QoS and traffic density aware location service technique called ZoomOut Location Service (ZLS). We have implemented ZLS in NS2.33. The simulation results for highway traffic show that ZLS updates its location servers in a uni-cast fashion such that the location servers have up-to-date information of advertised services and destination position. Similarly, a source can reach destination in the quickest possible way by sending uni-cast messages without using digital map or shortest path finding algorithms. Â© 2014 IEEE.